2013
DOI: 10.1038/nphys2636
|View full text |Cite
|
Sign up to set email alerts
|

Duality symmetry and its breakdown in the vicinity of the superconductor–insulator transition

Abstract: The superconductor-insulator transition (SIT) is an accessible quantum phase transition 1,2 that is observed in a number of systems and can be driven by various experimental means 3-9 . A central outstanding issue regards the physical nature of the insulating phase terminating superconductivity 10 . Theoretical advances led to the proposition that this insulator is a new state of matter, termed a superinsulator 11,12 , because its properties can be inferred from the superconductor by invoking duality symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 30 publications
7
57
0
Order By: Relevance
“…For each device, R (B, T, E = 0) data were used to test the scaling prediction, by varying B at small increments at fixed T. In figure 5, the T-scaling of R for the film is shown. A good visual collapse of the data is obtained for zν=1.12, which is close to the previous findings 6,35 . For the wires, R flattens and become T independent on either side of B c [figure2(b)], as low-T is approached.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For each device, R (B, T, E = 0) data were used to test the scaling prediction, by varying B at small increments at fixed T. In figure 5, the T-scaling of R for the film is shown. A good visual collapse of the data is obtained for zν=1.12, which is close to the previous findings 6,35 . For the wires, R flattens and become T independent on either side of B c [figure2(b)], as low-T is approached.…”
Section: Resultssupporting
confidence: 90%
“…In the superconducting side of the Btuned SIT, the power law is consistent with the collective pinning model of transport 22,34,36 and indicate the role played by interacting bosons (vortices) in transport. The existence of the power law behavior above B c , suggest that vortex transport might be important in the insulating state 34,35 . A quantum critical point is known to separate ground states with different symmetry.…”
Section: Resultsmentioning
confidence: 98%
“…In superconducting films close to the critical point, the low-bias resistance isotherms follow the finite size scaling model 4,5,16,17 , which gives strong indication that the SIT in films is also a quantum phase transition (QPT). In addition, it has been shown that in amorphous MoGe 5 and NbN 17 films, nonlinear differential resistance measured as a function of magnetic field at several finite bias voltages also scales both on the insulating and superconducting sides of the SIT.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies have examined evidence for duality (18,19) from resistivity measurements, but have not examined the full conductivity tensor across the transition. In this paper we provide insights concerning the nature of the H-SIT in highly disordered films, using new measurements of the full resistivity tensor across the quantum transition.…”
mentioning
confidence: 99%